Pemilih â€Hijauâ€ di Kota Santri: Kasus Pemilu 2004 di Pekalongan - Basyar, M. Hamdan (Jurnal Penelitian Politik, 2004)
The victory ofthe political party that carries the Islamic symbol or well known as the "green" (this is not to be confused with the green politics in ecological term) in the 2004 election in Pekalongan Regency, can not directly be implied that they will propose the "green" symbol (it is just like Islamic sharia, etc). The Pekalongan people and their influential leaders are more pragmatic to their interests than imposing the "green" politics. Furthermore, the Green didn't absolutely win in the local parliament. It has only a few more number than the "red" and "yellow" symbols. This means that the Green solidity is still questioned. A similar event of200I -when the election ofthe Mayor and the Deputy of Mayor was taken place- could happen again. In that time the Green was fragmented, fighting with their own individual or party interests. Therefore, the Pekalongan people needs to prove that their city deserve a called "the Santri City" -a city o f Islamic scholar-. The victory of the political party with the Green symbol doesn't have any effect yet, without real implementation in their daily life.